'Are You a Good Female Citizen?': Media Discourses on Self-Governing Represented in Popular Korean Weight-Loss Reality TV Shows. (June 2019) - Choi, Yoonso
Based on Foucault's work on governmentality, the purpose of this study is to examine the socio-cultural influences of media discourses that have been reproduced and spread in Korea's neo-liberal society through weight-loss reality TV shows. After neo-liberalism was established as a political ideology in Korea, weight-loss reality programs, which contain significant neo-liberal characteristics, have risen in popularity among ordinary Korean women. The popularity of female-oriented pop media culture has generated the idea of self-body care that now plays a powerful role in efficiently reproducing good female citizens who are able to be governed at a distance. This study particularly focuses on analyzing significant media discourse that tends to prompt ordinary girls and women into donning the role of a neo-liberal subject by taking care of their bodies. The major points include (1) producing a feminized, skinny body, rather than a healthy body; (2) defining clear boundaries between the normal and abnormal body by clothing size; (3) re-generating dominant female body discourse by a group of lifestyle designers; and (4) labeling female bodies that have failed in body-care. In conclusion, the study emphasizes significant cultural influences of the diet reality shows that operate as a cultural medium to efficiently produce a neo-liberal body.